Analisis Faktor-Faktor Yang Mempengaruhi Niat Individu Dalam Penggunaan Aplikasi Sistem Layanan Informasi Keuangan (SLIK) di Wilayah Kerja Malang - Luthfan Aufa Faqih; Hanifah Muslimah Az-Zahra; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Sistem Informasi Debitur (SID) is a means for debtors and creditors to view information related to historical individual debtor information (IDI) commonly known as BI Checking managed by Bank Indonesia (BI). Since January 1, 2018, SID service that was initially managed by BI is now managed by the Otoritas Jasa Keuangan (OJK) and replaced by the Sistem Layanan Informasi Keuangan (SLIK). However, based on a preliminary study, it is known that there are many bank financial services institutions that complain about SLIK. This research aims to find out the factors that influence individual intentions in the use of SLIK. The population of this study was SLIK users in Rural Credit Banks in the Malang working area. The number of respondents in this study amounted to 70 respondents who were selected using the purposive sampling method. Before the research questionnaire was distributed, expert judgment and pilot studies were conducted to test the validity and reliability of the questionnaire. After several invalid items were repaired or deleted, the questionnaire was distributed to the main respondent. The classic assumption test results show that the research data are normals and free from heterocedasticity. multicollinearism and autocorrelation. The results of multiple linear regression analysis show that the regression model proposed in this study has fulfilled the goodness of fit. In addition, the perceived usefulness variable has the effect of t and sig. (-1,872 and 0,066), perceived ease of use has an influence value of t and sig (2,682 and 0,009), security and privacy have an influence value of t and sig (2,756 and 0,008), technology readiness has the effect of t and sig (-1718 and 0.090). The four variables have influence partially or simultaneously on usage intention.